Archetypes of Inter-firm Relations in the Implementation of Management Innovation: A Set-theoretic Study in China's Biopharmaceutical Industry. Issue 1 (January 2014) - Meuer, Johannes
Innovation research increasingly focuses on understanding why and how firms implement new management practices, processes or structures. Emerging in the shadow of research on technological innovation, growing evidence points towards the inter-firm relation as an important locus of innovation. Yet although organizational theory suggests discrete alternative inter-firm coordination mechanisms, the literature on management innovation has thus far treated the inter-firm relation as one broad mode of organizing. This study takes a configurational perspective to identify archetypes of inter-firm relations leading to the implementation of management innovation. Using fuzzy set Qualitative Comparative Analysis (fsQCA) to analyse 56 firm partnerships in China's biopharmaceutical industry, the empirical evidence identifies four such discrete inter-firm archetypes: organic coalitions, bureaucratic foundations, coalitions of intense interdependency and reciprocal foundations. The results suggest that the type of interdependency, rather than the coordination mechanisms governing inter-firm relations, leads to the implementation of management innovation.